1981
DOI: 10.1111/j.1526-4610.1981.hed2101014.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐Dopa Effect on Prolactin Plasma Levels in Complicated and Common Migrainous Patients

Abstract: SYNOPSIS Dopamine is known as an inhibitor of Prolactin (PRL) secretion; Prostaglandin F 2a is known as a stimulatorof its production. These effects probably occur at the hypophisis. Prostaglandins are thought to be involved inthe mechanism of migraine attacks. Prolactin response (as plasma levels) to L‐dope inhibitory test wasmeasured in migrainous patients. Two different Prolactin curves were obtained during the migrainous attacks,according to the type of the migraine, common and complicated.It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…He noted high plasma levels of PRL during attacks and suggested that the reduction by the use of specific drugs might be a useful approach to treat these attacks. The release of PRL is inhibited by GABA at the anterior pituitary level (13)(14)(15)(16)(17)(18)(19)(20)(21)(22); sodium valproate may therefore inhibit PRL release and thus influence the migraine attack.…”
Section: Discussionmentioning
confidence: 99%
“…He noted high plasma levels of PRL during attacks and suggested that the reduction by the use of specific drugs might be a useful approach to treat these attacks. The release of PRL is inhibited by GABA at the anterior pituitary level (13)(14)(15)(16)(17)(18)(19)(20)(21)(22); sodium valproate may therefore inhibit PRL release and thus influence the migraine attack.…”
Section: Discussionmentioning
confidence: 99%
“…4 Also, several studies have been performed by means of dynamic tests of PRL secretion, by many workers. [5][6][7][8][9][10][11] These researches were carried on also after differential treatment periods, either using bromocriptine or 5-OH-tryptophan, methysergide or lisuride. 6,9 However, the results of all these studies did not reach agreement on the possible relationship between prolactin levels and migraine.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In the present study, we investigated the PRL response to thyrotropin-releasing-hormone (TRH) in female patients suffering from migraine, in the intervals between attacks and during an attack.…”
mentioning
confidence: 99%